225 The role of the dna damage response in vascular calcification. (5th June 2017) - Sun, Mengxi; Cobb, Andrew M; Hayward, Robert; Zhang, Qiuping P; Duer, Melinda; Shroff, Rukshana; Shanahan, Catherine M
Abstract : Introduction: Vascular calcification is a hallmark of vascular ageing, and associated with vascular smooth muscle cell (VSMC) death, phenotype modulation and maladaptation. However, it remains unclear how the initial stress signals link to these downstream cellular events. Emerging evidence and our in vitro data suggest that stress may drive vascular calcification through elevated levels of DNA damage, a key factor driving cellular ageing. Methods and Results: We investigated the effects of different DNA damage signalling pathway inhibitors (ATM, ATM/ATR and PARP1) on the progression of vascular calcification. Using comet assays and western blot, we found elevated levels of DNA damage in calcified VSMCs and that inducing DNA damage accelerated rates of calcification. Chemical inhibition or siRNA knockdown of ATM, ATM/ATR or PARP signalling reduced or delayed calcification and prevented cells undergoing calcification-associated phenotype changes including osteo/chondrogenic differentiation. Prevention was associated with down-regulation of senescence and inflammatory markers suggesting the senescence associated secretory phenotype (SASP) acts to potentiate VSMC calcification. Conclusion: Taken together, these in vitro data suggest DNA damage signalling is involved in the pathological regulation of calcification. Therefore, interventions that reduce DNA damage, promote DNA damage repair, or modulate DNA damage signalling could be potential therapies for the prevention of vascular calcification.